CMLHS Appreciation Night 2009: a night to inspire - UMP, CMLHS (Pusat Bahasa Moden dan Sains Kemanusiaan, 2009)
22 Oct 2009. The first CMLHS gala dinner, CMLHS Appreciation Night 2009, was held at Hyatt Regency Hotel, Kuantan.